PROTECTION IN RETAIL INVESTORS DISADVANTED BY FAKE TRANSACTION PRACTICE (CORNERING THE MARKET) (Faculty of Law, Universitas Negeri Semarang, 2018)
The practice of fake transaction is a stock trading practice that incurs many losses, especially for retail investors who basically do not control the market in majority on the floor of the stock. This practice may threaten the liquidity and credibility of capital market activities in Indonesia. Pseudo transaction is one of the crimes prohibited in Capital Market Law which fall into the category of market manipulation. In simple terms, market manipulation is an activity undertaken by a person either directly or indirectly creating a false or misleading image of a trading activity, market situation, or price of Securities at a Stock Exchange or giving a statement, or an improper, or misleading statement so that the price of the securities in bursa affected. Provisions on market manipulation are provided in Articles 91, 92 and 93 of Law Number 8 of 1995 concerning the Capital Market.Keywords : Concerning the market, Ritel Investors, Protection